Cholesterols Work as a Molecular Regulator of the Antimicrobial Peptide-Membrane Interactions - Li, Jia; Lu, Xuemei; Ma, Wendong; Chen, Zhonglan; Sun, Shuqing; Wang, Qinghui; Yuan, Bing; Yang, Kai (Frontiers in Molecular Biosciences, 2021)
The existing cholesterols (Chols) in animal cell membranes play key roles in many fundamental cellular processes, which also promise the possibility to modulate the bioactivity of various membrane-active biomacromolecules. Here, combining dynamic giant unilamellar vesicle leakage experiments and molecular dynamics simulations, the inhibitory effect of Chols on the membrane poration activity of melittin (Mel), a typical natural antimicrobial peptide, is demonstrated. Molecular details of the Mel-Chol interactions in membrane show that, for a Chol-contained lipid membrane, Mel exposure would perturb the symmetric bilayer structure of the membrane and specifically influence the location and orientation distributions of Chol molecules to an asymmetric state between the two leaflets; moreover, the Mel-Chol interactions are significantly influenced by the membrane environment such as unsaturation degree of the lipid components. Such inhibitory effect is normally ascribed to an accumulation of Chol molecules around the membrane-bound peptide chains and formation of Chol-Mel complexes in the membrane, which hinder the further insertion of peptides into the membrane. This work clarifies the molecular interactions between membrane-active peptides and Chol-contained membranes, and suggest the possibility to develop targeted drugs due to the membrane component specificity between bacterial and animal cells.